Dismissal policies for vaccine refusal among US physicians: a literature review - Tamara B. Garcia; Sean T. O'Leary (Taylor & Francis Group, 2020)
Childhood vaccination is one of the greatest public health achievements of the 20th century, yet increasingly, parents question the safety of and need for vaccines. This has led to increased rates of vaccine delay and refusal and outbreaks of vaccine-preventable diseases. Physicians struggle with how to respond to families who refuse vaccines, as there are few known effective interventions to convince a family to vaccinate. In the United States, the practice of dismissing families for vaccine refusal appears to be increasing as a strategy for dealing with vaccine refusal. In this review, we review the literature surrounding this controversial practice, starting with the impact that vaccine-refusing families have on medical practices, followed by a review of dismissal policies of US physicians, and ending with a discussion of the ethics of this practice.